The Effects of N-Acetylcysteine on the Rat Mesocorticolimbic Pathway: Role of mGluR5 Receptors and Interaction with Ethanol - Sandra Fernández-Rodríguez; Claudia Esposito-Zapero; Teodoro Zornoza; Ana Polache; Luis Granero; María José Cano-Cebrián (MDPI AG, 2021)
N-acetylcysteine (NAC) is a prodrug that is marketed as a mucolytic agent and used for the treatment of acetaminophen overdose. Over the last few decades, evidence has been gathered that suggests the potential use of NAC as a new pharmacotherapy for alcohol use disorder (AUD), although its mechanism of action is already being debated. In this paper, we set out to assess both the potential involvement of the glutamate metabotropic receptors (mGluR) in the possible dual effect of NAC administered at two different doses and NAC's effect on ethanol-induced activation. To this aim, 30 or 120 mg/kg of NAC was intraperitoneally administered to rats with the presence or absence of the negative allosteric modulator of mGluR5 (MTEP 0.1 mg/kg). Thereafter, the cFOS IR-cell expression was analyzed. Secondly, we explored the effect of 120 mg/kg of NAC on the neurochemical and behavioral activation induced by intra-VTA ethanol administration (150 nmol). Our results showed that the high NAC dose stimulated cFOS expression in the NAcc, and that this effect was suppressed in the presence of MTEP, thus suggesting the implication of mGluR5. Additionally, high doses could attenuate the ethanol-induced increase in cFOS-expression in the NAcc, probably due to a phenomenon based on the long-term depression of the MSNs. Additional experiments are required to corroborate our hypothesis.